KERJASAMA PENGEMBANGAN POTENSI WISATA SUNGAI DI DESA MENURAN KECAMATAN BAKI - Kurniawan Kurniawan; Riana Rachmawati Dewi; Elvina Elvina; Syahna Utami Nisa (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
Village tourism is a group of people who are able to interact and work together in empowering existing potential. Using the land as a tourist village location in the district. Sub district Baki Sukoharjo is always developed. UNIBA Surakarta Students, Association Team conducted research and saw the potential for tourism in a Menuran Village with the River as the main key. The problem faced is the lack of technology utilization training, improvement of facilities and infrastructure around the location. The method used is the approach and direction to the community groups through socialization and training and improvement of facilities and infrastructure in the form of health sanitation facilities and the procurement of tourist boats. The result of this program is the river tourism village in Menuran where the community is increasingly creative and managing the potential of the river as an educational tour for the community to preserve and maintain the river .